Surface Water Quality Trends and Regression Model through SPSS in Udaipur, Rajasthan - Choudhary, Sangeeta (PREPARE@u® | IEI Conferences, 2021)
The surface water quality status and trend of Udaipur’s main lakes namely, Fatehsagar, Pichola Lake, and Udaisagar has been identified through 10 years of data collected from ENVIS Centre under on Control of Pollution of Water, Air, and Noise, hosted by Central Pollution Control Board. Water quality data were collected for the parameters like BOD, DO, pH, Conductivity, NN, Fecal coliform, Total coliform to determine the water pollution level and water treatment requirements. Overall water quality status has been improved from 2016 to 2019 due to the wastewater treatment plant. Udaisagar is the most polluted lake among the three lakes. Fecal coliform was suddenly increased in 2018 due to leakage of sewage line near Pichola Lake. These lakes are interconnected and very useful for drinking, industrial, agricultural, and tourism purposes and proper maintenance will be helpful for all dimensional growth of the city. A regression model for BOD was also developed for these lakes. Dependency of Temperature, pH, Dissolved oxygen, NN, Fecal coliform, and Total coliform was checked on BOD through SPSS multiple regression analysis. It is found that only Temperature and Total Coliform affect the values of BOD. The variance analysis showed p-values of < 0.05 and no multicollinearity was diagnosed, with VIF values of < 10.